Interaction of vitamins with mental performance - Helmut Heseker and Werner Kübler and Volker Pudel and Joachim Westenhöfer (Bibliotheca Nutritio et Dieta, 1995)
In the presence of a chronically insufficient vitamin supply which was verified by repeated measurements of the vitamin parameters, many unfavorable psychometric findings in the corresponding deficiency groups are observed for the vitamins C, thiamin, riboflavin, cobalamin and folate, depending on the degree of the insufficient vitamin supply. Vitamin supplementation in cases of initially insufficient vitamin supply indicate some effects in the sense of an improvement of behavior and cognitive functions. Supplemental vitamin intake in physiological dosages in addition to a vitamin-sufficient diet did not lead to an improvement of behavior and mental performance.